(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The term ‘Competency’ means the ability or skill to perform certain task in successful and efficient manner. But, the concept of ‘Digital Competency’ has wider dimension and consisting the knowledge, skills and attitude while using ICT in delivering services to the citizens. It is multi-dimensional and complex concept, constantly changing with the development of digital media, appraisal/ values, complex span of skills and knowledge formative education, and openness for all possible interpretation and area of use are considered as the dimension of digital competencies.India has evolved its ICT based governance in the year of 1970 with the establishment of Department of Electronics at National level with the objectives to brought information and communication in daily use. It strengthened the e- Governance with the help of National e- Governance Plan (NeGP) at the central level. The ‘Digital India’ is also an ambitious program me of Government of India launched on July 1, 2015 having the vision to empower the citizens of country and to develop skills and capacity for handling the digitalized information.The present paper is based on the experiences of delivering “Driving License” at e- Dishacentre at Kurukshetra District of Haryana State to its citizens. An effort has been made in this paper to assess the coverage, utilization of database resources and sharing of the resources available in different governmental entities, delivery of documents protection and preservation of confidential information and redressal grievances, if any, are examined based on empirical information collected during investigation at e- Datacenter.